The Correlation between Indonesian Students’ Vocabulary Mastery and Their Reading Comprehension - Amal Hayati (AT-TA'LIM, 2016)
Exploring students’ background knowledge in pre-reading activities suggests the importance of interaction in the process of meaning making which requires appropriate vocabulary. Although many factors constitute students’ comprehension, vocabulary should be the main concern in EFL reading classes.  Consistence with this premise, the current study was aimed at proving the correlation between students’ vocabulary mastery and their reading achievement at the fourth semester of STKIP Dharma Bakti Lubuk Alung. This correlational study involved 70 students taken through cluster random sampling. Vocabulary and reading test were employed to determine the correlation between students’ vocabulary mastery and their reading comprehension.  Through Correlation of Product Moment, coefficient correlation between two variables was found to be 0.61 with index correlation in r-table was 0.1617 for α= 0.05, suggesting that the coefficient correlation between two variables (rxy) t-calculated was bigger than t-table.  It means that H1 was accepted and H0 was rejected. In conclusion, there was a positive correlation between students’ vocabulary mastery and their reading comprehension at the fourth semester students of STKIP Dharma Bakti Lubuk Alung